A Silicon‐Stereogenic Silanol ‐ 18O‐Isotope Labeling and Stereogenic Probe Reveals Hidden Stereospecific Water Exchange Reaction. Issue 1 (10th November 2022) - Langenohl, Felix; Rösler, Jonas; Zühlke, Sebastian; Kirchhoff, Jan‐Lukas; Strohmann, Carsten
Abstract: A silicon‐stereogenic aminosilanol was isolated in excellent diastereomeric ratio and the absolute configuration was determined. The silanol is configurative and condensation stable in solution and shows stereoselective transformations with a clean stereospecific pathway in follow‐up reactions, which leads to the isolation of a silicon‐stereogenic zinc complex and siloxane compounds. Investigations with 18 O‐labelled water and mass spectrometry analysis revealed an otherwise hidden exchange of oxygen atoms of silanol and water in solution that proceeds with retention of the configuration at the silicon center. This novel combination of a stereochemical probe and isotopic labeling in a silicon‐stereogenic compound opens new analytic possibilities to study stereochemical courses of reactions with the aid of chiral silanols mechanistically. Abstract : Silanols are important industrial building blocks for the functionalization of surfaces. In this research, one silicon‐stereogenic silanol was selectively synthesized and analyzed. By using an innovative combination of this stereochemical probe and isotope labeling, a configurationally stable chiral silanol was studied, providing new insights into mechanistic studies.